Cutaneous reactions to anticoagulants - Harenberg, Job; Hoffmann, Ursula; Huhle, Günter; Winkler, Markus; Bayerl, Christiane (American journal of clinical dermatology, 2001)
Anticoagulant-induced skin reactions appear as allergic or necrotic responses to vitamin K antagonists or heparins. Cutaneous allergy has been reported with danaparoid sodium and flush reactions have been seen with hirudins. The pathogenesis of the reactions differs between drugs. Generally, they occur between days 3 to 10 after the start of treatment, but may also occur later. In patients experiencing necrosis with a vitamin K antagonist, concomitant protein C deficiency, protein S deficiency or lupus anticoagulant has been described, whereas the precise mechanism of the other reactions is unknown. In patients with allergic reactions to heparins, cutaneous tests may help to identify alternative anticoagulants. Such a test cannot be performed in patients with skin necrosis.